Effect of Altered Canopy:Root Volume Ratio on Grapevine Growth Compensation - Hunter, J.J.; Volschenk, C.G. (South African Journal of Enology and Viticulture, 2017)
Nine-year-old, intensively irrigated, 3.0 x 1.2 m spaced and vertically trellised (5-strand) Chenin blanc/99 Richter vines were converted to double the original cordon length by either removing alternate vines or by implementing a Lyre trellising system. In the former case the root volume was doubled, whereas in the latter case it was kept the same as for the non-converted vines. After five years, a root profile study showed that roots of the single-cordoned, vertically trellised vines with extended cordon were distributed beyond the original soil volume (before conversion); this was not the case for the Lyre system. No difference in root density occurred between vines of converted systems.  The available soil volume was apparently better colonised by roots of the converted systems, mainly because of an increase in fine roots. The greatest reduction in individual shoot growth was found for vines trained to the Lyre system. Yield per vine varied according to cane mass. Yield per hectare of vines trained to the vertical trellis with extended cordon space and the Lyre system increased significantly. Yield:cane mass ratios of 11, 15 and 16 were found in the case of the vertical, the vertical with extended cordons and the Lyre systems, respectively. The results indicated that shoot growth was better accommodated and distributed by extending cordon length, particularly when the ratio of cordon length to root volume was increased (as for the Lyre system). Compensatory growth occurred when both above-ground and subterranean growth volumes were increased. Preventing compensatory growth by the root system, resulted in balanced growth and improved microclimatic conditions for pest and disease control and grape ripening.  This principle may be implemented as a long-term solution to problems associated with excessive vigour.